Pelaksanaan Perhitungan Draft Survey dalam Menghitung Jumlah Muatan di Atas Kapal MV. Silver Sailing : Penelitian - Muhammad Hendry Surya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Draft survey is a method for measuring a ship's cargo quantity by calculating the difference in the vessel's displacement before and after loading or unloading, based on the draft (the depth of the ship's hull submerged in water). This study aims to examine the implementation of draft survey calculations on the MV Silver Sailing to accurately determine cargo quantity. The method involves measuring the draft at six standard points, applying trim and list corrections, calculating displacement using the hydrostatic table, and deducting elements such as fuel, ballast water, and freshwater through tank sounding. The results show that draft surveys can provide highly accurate cargo weight estimates. Draft surveys serve as an efficient solution for loading and unloading operations, particularly for bulk cargo, and are crucial in supporting smooth maritime logistics and trade operations.